MAPPING OF SOCIAL CUSTOMER RELATIONSHIP MANAGEMENT WITH ELECTRONIC CUSTOMER RELATIONSHIP MANAGEMENT - Arshi Naim (Journal Park Publishing, 2022)
The rapid rise of powerful social customers has drastically changed the ECRM background. Social CRM (SCRM) emerged as an ECRM for companies to enable customer relationship management (with social customers) utilizing social technology. Despite the many applications that are labeled as SCRM, there is a lack of guidelines for SCRM design and development. Good customer relationship can bring great benefits and a competitive advantage to organization. The purpose of this study is to map SCRM with ECRM for fast moving consumer goods while focusing on customer centric approach. In the chapter focuses on different ECRM key factors and their relationship in order to improve customer relationship through the use of ECRM. Our conclusion is that in order to improve the performance of ECRM, an organization should choose ECRM technology that suits with organization strategy and practice as well as employees’ technology and service capabilities.
Keywords: Electronic Customer Relationship Management (ECRM); ECRM technology; Social CRM